111k views
24 votes
Write an algebraic expression for

the verbal expression:
"5 times the sum of a squared and
b minus 3 times the sum of
a and b".​

User Sudharshan
by
5.4k points

1 Answer

8 votes

Answer:

"5 times the sum of a squared and b minus 3 times the sum of

a and b".​

  • 5(a²+b) - 5(a+b)

which can be simplified such as:


5\left(a^2+b\right)-5\left(a+b\right)=5a^2-5a

Explanation:

Given the verbal expression

"5 times the sum of a squared and b minus 3 times the sum of

a and b".​

BREAKIN DOWN THE STATEMENT:

The sum of 'a' Squared and 'b' = a²+b

  • 5 times the sum of a squared and b = 5(a²+b)

The sum of a and b = a+b

  • 3 times the sum of a and b = 5(a+b)

Now, "5 times the sum of a squared and b minus 3 times the sum of

a and b".​

  • 5(a²+b) - 5(a+b)

Let us simplify the algebraic expression


5\left(a^2+b\right)-5\left(a+b\right)


=5a^2+5b-5a-5b

simplify


=5a^2-5a

Thus,


5\left(a^2+b\right)-5\left(a+b\right)=5a^2-5a

User Zeeshanhirani
by
6.4k points